MFRS 9 financial instruments: classification and measurement of financial assets / Aniza@Marzita Ishak and Roshidah Safeei - Ishak, Aniza@Marzita; Safeei, Roshidah (Faculty of Accountancy, UiTM Kedah, 2019)
MFRS 9 is equivalent to IFRS 9 Financial Instruments as issued by IASB in July 2014. MFRS 9 replaced MFRS 139 Financial Instruments: Recognition and Measurement from 1 January 2018 to improve accounting for financial instruments. Among significant changes in the MFRS 9 relates to the classification and measurement of financial assets.